Determination of the Accurate Flow Formula of a Hydrodynamic Incomplete Cooled Well According to the Degree of Mud Opening - Mammadova, G.G. (Herald of Azerbaijan Engineering Academy, 2025)
In the article, a given well with a flat bottom, hydrodynamic ally incomplete according to the degree of formation opening, the bottom is replaced by a well with a bottom in the form of a concave hemispherical surface, and the exact full discharge formula of the given well is derived. Here, the layer is saturated with non-Newtonian oil and consists of two parts, a flat-radial flow occurs in the upper part with a thickness a, and a complex percolation flow occurs in the lower part with a thickness h, the percolation law A. Krasnopolski is non-linear. After replacement, a hemispherical-radial simple percolation flow occurs in the lower part of the layer, and the flow lines are radial straight lines; and equipotential surfaces are concentric hemispheres. Two different stationary hydrodynamic problems were solved and discharge formulas were derived for both parts of the reservoir separately. By summing these two debits, the exact debit formula of the given flat-bottomed well was obtained.